Clinical burden of pneumonia, meningitis and septicemia in Norway 2 years after 7-valent pneumococcal conjugate vaccine introduction. Issue 6 (August 2015) - Munson, Samantha; Raluy-Callado, Mireia; Lambrelli, Dimitra; Wasiak, Radek; Eriksson, Daniel; Gray, Sharon
Aims: This population-based, retrospective study quantified the rates of all-cause and pneumococcal pneumonia, meningitis and septicemia in Norway from 2008 to 2009 and determined the proportions of cases caused by pneumococcal vaccine serotypes. Methods : Data on patients with all-cause and pneumococcal pneumonia, meningitis and septicemia were obtained from the Norwegian Patient Registry, which collects hospitalization data from all Norwegian public hospitals based on International Classification of Diseases codes. Norwegian Patient Registry case records linked to the Norwegian Surveillance System for Communicable Diseases provided serotype data for invasive pneumococcal disease in patients with microbiological cultures. Results : In 2008 and 2009, hospitalization rates were relatively stable for all-cause pneumonia (5.28 and 5.35, respectively, per 1000), meningitis (10.70 and 9.67, respectively, per 100, 000), and septicemia (from 171.81 to 161.46 per 100, 000). In contrast, rates decreased for International Classification of Diseases-10 diagnosed pneumococcal pneumonia (from 13.66 to 10.52 per 100, 000), although these cases may be under-reported because of inclusion in all-cause pneumonia. Rates also decreased in diagnosed pneumococcal meningitis (from 1.60 to 1.19 per 100, 000) and diagnosed pneumococcal septicemia (from 9.08 to 7.94 per 100, 000). Diagnosed pneumococcal disease rates were highest in younger children and older adults, peaking at ⩾60 years old. Pneumococcal pneumonia, meningitis and septicemia caused by serotypes included in the 7-valent pneumococcal conjugate vaccine decreased substantially during the study period, with corresponding serotype replacement by non-7-valent pneumococcal conjugate vaccine serotypes. Conclusions : From 2008 to 2009, International Classification of Diseases-10 diagnosed pneumococcal pneumonia, meningitis and septicemia decreased in most age groups but remained greatest among subjects aged 0–1 and ⩾60 years.